(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2020)
Difficulties in learning of reading can occur because the absence of reinforcement to establishment of reading, during the initial steps. The study aimed teach the textual comprehension through systematic arbitrary reinforcement with children with typical development. The participants were divided in two groups: experimental (N=4) and control group (N=4). In each teaching the children read a book, answered the comprehension questions and answered the Cloze test. The medium results of experimental group were bigger than results of control group of pos-test (50% of increment in pos-test of experimental group and 18,6% of control at comprehension questions; 33% of increase at Cloze test of experimental group and 16,6% of control group. The results indicated the efficacy of teaching procedure.